St. Lucia : Climate Change Policy Assessment. (IMF Staff Country Reports; Country Report ;, 2018)
This paper takes stock of St. Lucia's plans to manage climate change, from the perspective of their macroeconomic implications, and suggests macro-relevant reforms that could strengthen the likelihood of success of the national strategy. To meet its renewable energy plans, St. Lucia will need to mobilize private investment. External assistance will be needed to develop supporting infrastructure. Building capacity for project assessment and investment promotion is a high priority, to shape needed investments into bankable projects. Elsewhere, capacity-building would be most useful to help cost sectoral plans, complete the disaster-preparedness strategy, move toward carbon taxation, and strengthen skills in public investment management and public financial management.